2022
DOI: 10.2196/28858
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing Artificial Intelligence for Health Message Generation: The Folic Acid Message Engine

Abstract: Background Communication campaigns using social media can raise public awareness; however, they are difficult to sustain. A barrier is the need to generate and constantly post novel but on-topic messages, which creates a resource-intensive bottleneck. Objective In this study, we aim to harness the latest advances in artificial intelligence (AI) to build a pilot system that can generate many candidate messages, which could be used for a campaign to sugge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 86 publications
(86 reference statements)
1
16
0
Order By: Relevance
“…Results revealed that temperature sampling (version 5, t=0.7) and a hybrid approach (version 1, p=0.9, k=50, t=0.8; version 8, k=40, t=0.7) exhibited perplexity scores closely to that of the expert-writing condition. Consistent with prior studies [ 28 , 33 , 73 , 80 ], decoding methods with higher p values (version 2, p=0.9; version 3, p=0.95) or higher temperature settings (version 4, t=0.9) were found to sample too many unlikely tokens, resulting in messages that were diverse yet incoherent. The perplexity findings also echoed the repetition filtering process: decoding methods (version 1, 5, 8) that exhibited lower and approximating-reference perplexity scores had a higher proportion of messages (7.2% to 7.7%) discarded due to repetition; conversely, decoding methods with higher perplexity scores (version 2, 3, 4) demonstrated lower rates of repetition (3.7% to 4.5%).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Results revealed that temperature sampling (version 5, t=0.7) and a hybrid approach (version 1, p=0.9, k=50, t=0.8; version 8, k=40, t=0.7) exhibited perplexity scores closely to that of the expert-writing condition. Consistent with prior studies [ 28 , 33 , 73 , 80 ], decoding methods with higher p values (version 2, p=0.9; version 3, p=0.95) or higher temperature settings (version 4, t=0.9) were found to sample too many unlikely tokens, resulting in messages that were diverse yet incoherent. The perplexity findings also echoed the repetition filtering process: decoding methods (version 1, 5, 8) that exhibited lower and approximating-reference perplexity scores had a higher proportion of messages (7.2% to 7.7%) discarded due to repetition; conversely, decoding methods with higher perplexity scores (version 2, 3, 4) demonstrated lower rates of repetition (3.7% to 4.5%).…”
Section: Discussionsupporting
confidence: 83%
“…Similarly, Holtzman et al [ 34 ] observed that temperatures exceeding 0.9 yielded messages diversity akin to human writing, measured by self-BLEU scores, and temperatures above 0.7 effectively mitigated repetition issues. In the healthcare context, Schmalzle and Wilcox [ 80 ] conducted a pilot test employing temperature settings of 0.3, 0.5, 0.7, and 1 with a fine-tuned 355M GPT-2 model, aiming to create messages about folic acid. Their results indicated that T=0.7 produced the most balanced outputs in terms of both quality and diversity, whereas T=1 led to incoherent outputs and T<0.5 produced text that was highly homogeneous with the training text.…”
Section: Study Ii: Decoding Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…As an essential nutrient, its significance for the well-being of pregnant women is self-evident. [30][31][32][33] In this study, the selected subjects exhibit varying degrees of FA supplementation, contributing to a reduction in the risk of fetal malformations among pregnant women to a certain extent.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only one paper in communication has used NLP models to generate health awareness messages. Schmälzle and Wilcox (2022) introduced a message machine capable of creating new awareness messages. Specifically, they used a GPT2-LM to generate short topical text messages, now commonly called tweets.…”
Section: Using Ai To Generate Health Awareness Messagesmentioning
confidence: 99%